Breeding Whooper Swans Cygnus cygnus in Latvia, 1973-2009 - Boiko, Dmitrijs; Kampe-Persson, Hakon (Wildfowl, 2013)
This study describes the population status, development, distribution and habitat choice of breeding Whooper Swans Cygnus cygnus breeding in Latvia. The breeding population increased from one breeding pair in 1973 to c. 260 pairs in 2009. The first pair of Whooper Swans nested in the western part of the country, and this area has remained a stronghold for the species within Latvia, supporting 86% of 256 sites where breeding was confirmed during the years 2000–2009, with 54% of pairs found in the districts of Liepaja, Talsi and Kuldiga. Most breeding sites were associated with small water-bodies: 77% were at artificial ponds and 17% at beaver dams. Few nests were found in lakes, mires, bogs and gravel pits. Results are discussed in relation to the increase in Whooper Swan numbers in other parts of Europe.